2017
DOI: 10.5487/tr.2017.33.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Carcinogen-Activating Cytochrome P450 Enzymes by Xenobiotic Chemicals in Relation to Antimutagenicity and Anticarcinogenicity

Abstract: A variety of xenobiotic chemicals, such as polycyclic aromatic hydrocarbons (PAHs), aryl-and heterocyclic amines and tobacco related nitrosamines, are ubiquitous environmental carcinogens and are required to be activated to chemically reactive metabolites by xenobiotic-metabolizing enzymes, including cytochrome P450 (P450 or CYP), in order to initiate cell transformation. Of various human P450 enzymes determined to date, CYP1A1, 1A2, 1B1, 2A13, 2A6, 2E1, and 3A4 are reported to play critical roles in the bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…CYP1A2 was the only phase 1 DME that showed a different trend by increasing. CYP1A2 metabolizes various environmental procarcinogens, such as heterocyclic amines, nitrosamines, and a atoxin B 1 [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP1A2 was the only phase 1 DME that showed a different trend by increasing. CYP1A2 metabolizes various environmental procarcinogens, such as heterocyclic amines, nitrosamines, and a atoxin B 1 [28].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A2 is important for the metabolism of endogenous substrates [36] and activation of many environmental carcinogens including dietary heterocyclic amines, certain mycotoxins, tobacco-speci c nitrosamines, and aryl amines [28]. It has been suggested that sustained induction of CYP1A2 for example, maybe bene cial in women, as through 2-hydroxylation it increases estrogen clearance to antioestrogenic metabolites, so acting to protect against estrogen-driven tumors [37].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1B1 is highly expressed in oestrogen target tissues and catalyses the metabolic activation of several procarcinogens (e.g., heterocyclic amines, polycyclic hydrocarbons) and the 4-hydroxylation of 17β-oestradiol [27,28] . It is also abundant in tumour tissues.…”
Section: Cyp1b1mentioning
confidence: 99%
“…The molecules present in tobacco and tobacco smoke begin to act in the body only after enzymatic activation that can be achieved by cytochrome P450 2A13 (P450 or CYP) and is considered a key reaction pathway for initiation of bioactivation of carcinogenesis, and consequently of the progressive changes in the biological profile of the cell [13,14].…”
Section: Introductionmentioning
confidence: 99%